Pendidikan Interkultural di Sekolah Melalui Pembelajaran Bahasa dan Sastra Indonesia Sebagai Pembentuk Ruang Nasionalisme Dinamis - Eka, Scarletina Vidyayani; Setiawan, Fredy Nugroho; Rozin, Muhamad (Studi Budaya Nusantara, 2018)
Abstract Indonesia consists of individuals who have diverse cultural, religious, ethnic and linguistic backgrounds. With the escalation of social problems nowadays, there needs to be a new space for society in which the values of harmony, tolerance and cohesion are nurtured. The government through schools seeks to instill these values. One of the efforts that can be made by schools is through intercultural education. Intercultural education can be integrated into various aspects of school activities, one of which is the teaching of Indonesian Language and Literature subject. Here, the authors attempt to map the extent to which the concept of intercultural education is present through the teaching materials by conducting a case study at SMAN 3 Malang. To analyze the concept of intercultural education at SMAN 3 Malang, the authors reviewed the literary teaching materials used by the teachers and observed the Teaching and Learning Activities in the classrooms. The results of the analysis show that the literary teaching materials used at SMAN 3 Malang already contain the competencies of intercultural education and the concept has been applied in the teaching and learning process. These results are in line with the Core Competencies and Basic Indonesian language Competencies outlined by the Government in an effort to form the space of tolerant and harmonious Indonesian society.